2021
DOI: 10.1530/erc-20-0435
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations in Hürthle cell nodules and preoperative cancer risk

Abstract: Hürthle cell carcinoma (HCC) is a distinct type of thyroid cancer genetically characterized by DNA copy number alterations (CNA), typically of genome haploidization type (GH-type). However, whether CNA also occur in benign Hürthle cell adenomas (HCA) or Hürthle cell hyperplastic nodules (HCHN), and have diagnostic impact in fine needle aspiration (FNA) samples, remains unknown. To address these questions, we (i) analyzed 26 HCC, 24 HCA, and 8 HCHN tissues for CNA and other mutations using ThyroSeq v3 (TSv3) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
4
33
2
1
Order By: Relevance
“…With this limitation with every additional centimeter of nodule size, malignancy odds were reported to be increased by 1.9 (95% CI, 1.3-2.7; P = .001). 10,11 Consistent with our prior report, among FNHCT nodules with GH-CNA only, resected nodules were on average approximately 1 cm larger than the clinically observed ones. Furthermore, among resected nodules, GH-CNA-positive thyroid cancers were approximately 2.3 cm larger than GH-CNA-positive FOAs.…”
Section: Cancer Cytopathology October 2021supporting
confidence: 90%
See 2 more Smart Citations
“…With this limitation with every additional centimeter of nodule size, malignancy odds were reported to be increased by 1.9 (95% CI, 1.3-2.7; P = .001). 10,11 Consistent with our prior report, among FNHCT nodules with GH-CNA only, resected nodules were on average approximately 1 cm larger than the clinically observed ones. Furthermore, among resected nodules, GH-CNA-positive thyroid cancers were approximately 2.3 cm larger than GH-CNA-positive FOAs.…”
Section: Cancer Cytopathology October 2021supporting
confidence: 90%
“…Our results in this large series of FNHCT confirm that GH-CNA represents a molecular signature of follicular oncocytic neoplasms, including both benign FOA and malignant FOCa or EOFVPTC, but is absent in oncocytic metaplasia. 10 The reported preoperative risk of cancer for nodules with GH-CNA varies depending on nodule size. Clinically observed nonresected nodules tend to be smaller.…”
Section: Cancer Cytopathology October 2021mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examined whether known thyroid oncogenes and tumor suppressor genes were recurrently mutated in HCC. Two studies reported recurrent RET-PTC translocations in HCCs using FISH and PCR methods (18,19). However, in larger cohorts using DNA-sequencing based methods, RET-PTC (CCDC6-RET and NCOA4-RET) translocations were not detected, nor were RET-PTC translocations recurrently identified in molecular testing of FNA specimens with Hürthle cell cytology (20-26).…”
Section: Low Frequency Of Canonical Fdtc Driver Mutationsmentioning
confidence: 99%
“…HCCs harbor mutations in known thyroid cancer oncogenes including RAS , TSHR , EIF1AX , TP53 , PTEN , BRAF , PAX8-PPARγ , and MEN1 ( 20 , 22 31 ). However, mutations in these genes occur in a small fraction of HCC.…”
Section: Low Frequency Of Canonical Fdtc Driver Mutationsmentioning
confidence: 99%